Implementation of the Low-cost Islamic Peer to Peer Financing Model in Student Entrepreneurship Financing Applications - Rahmat, Biki Zulfikri; Rachman, Andi Nur; Dewi, Euis Nur Fitriani; Alwin, Muhammad (School of Applied Science, Telkom University, 2024)
Currently, there are many applications of technology-based financial funding, and some have even been legalized by the Financial Services Authority (OJK), which is called fintech. In reality, it is still burdensome for business actors because of the difficulty in paying the installments that must be borne, whereas the business will have funds only if the goods they are selling are sold. In the Siliwangi University campus environment, students are required to take entrepreneurship lectures. So far, the learning process activities have only been in the form of concepts and theories; this has become an obstacle to field practice. In the field of entrepreneurship, these students become business actors. However, there is a difficulty in practicing entrepreneurship since students' capital is limited. On this issue, the campus is obliged to facilitate the creation of an entrepreneurial learning process as an investor. To connect the entrepreneurship learning process, information technology is needed. The application is intended to assist in the process of providing business capital by applying the concept of Islamic economics, namely the Islamic peer to peer financing model. This model provides flexibility between business actors and investors in providing financial assistance with potential profits and losses shared together. Based on the above problems, to support student entrepreneurship programs, it is necessary to apply financing for entrepreneurship program assistance based on the Islamic peer to peer financing model. From the results of testing the application can be applied to support the student entrepreneurship learning process based on the respondent's score of 82.08333 which indicates that the System Usability Scale value for this application is Acceptable.